Endoscopic Dilatation of Meatal Stenosis of Ureterocele in Adult Patients: An Easy and Innovative Technique with Literature Review - Basiri, Abbas; Bonakdar Hashemi, Milad; Aslani, Arsalan (Urology Journal, 2020)
This study presents initial experience in endoscopic meatal dilatation of obstructive ureterocele in adult patients. During cystourethroscopy, we tried to find the orifice of ureterocele, passed a guide wire and introduce an 8 Fr ureteroscope in to the ureterocele orifice, going up to the renal pelvis as under vision dilatation of ureterocele meatus. Two Double-J stent were inserted and remained for six weeks to keep the meatus dilated. Adverse effect of endoscopic management was decreased due to minimal anatomic changes. Patients’ symptoms were relieved and no evidence of new onset vesico-ureteral reflux and obstruction were seen after up to one-year follow-up. Endoscopic meatal dilatation of stenotic ureterocele in adult patients is safe and effective thus, trying to find the orifice of ureterocele is suggested.